In the eye of the (fire) storm: better safe or sorry? - Neves, Hélder António (2019)
In the past, Word of Mouth used to be overlooked and undervalued by marketers as a legitimate marketing strategy, but nowadays, organizations incentivize consumers to engage in online conversations. Over the last few years, the investments made on social network sites have increased significantly. Nevertheless, all these efforts can be seriously compromised once a social media crisis arises. Online firestorms, as termed by Pfeffer et al. (2014), pose serious threats to people, companies, or groups in social media networks, and thus must be addressed carefully and thoroughly. Considering the characteristics and dynamics of social media, this sudden discharge of large quantities of negative WOM and complaint behaviour, often paired with intense indignation, can occur at a staggering pace, jeopardizing the sustainability and even the subsistence of its target. The present research used a 2 x 3 factorial experimental design, that comprised two levels of image repair strategies (corrective action; apology), and three levels of online firestorm triggers (unethical behaviour; core business problem; communication issue). An online questionnaire was distributed, and 564 responses were obtained, whose objective was to investigate the effect of the image repair strategy employed by an organization under attack following an incident, on Facebook users’ perceptions, forwarding and negative WOM intentions. Results indicated that a response strategy that incorporates a corrective action, as image repair strategy, is more effective than a response strategy that incorporates an apology following core business- and communication-related incidents, whilst none of the strategies under analysis showed to be more effective than the other one following unethical behaviourrelated incidents. Furthermore, the effect of image repair strategy on perceptions, forwarding and negative WOM intentions is moderated and mediated by Facebook users’ attributed responsibility and brand attitude, respectively. Last, the absence of an organizational response following an incident has a negative effect on Facebook users’ brand attitude.